The relationship between preschool inclusive teachers' perception of traditional culture and digital literacy: The chain mediating role of technology acceptance and job insecurity - Xuezhen Feng; Wenjun Guan; Enwei Xu (Acta Psychologica, 2025)
The digital literacy of preschool inclusive educators is a core factor and key issue in ensuring the quality of early childhood education and achieving educational equity. This study explores the impact of preschool inclusive teachers' cognition of traditional culture on their digital literacy, as well as the chain-mediating role of technology acceptance and job insecurity in this relationship. Through a questionnaire survey, valid data were collected from 500 teachers in 40 preschool inclusive kindergartens. The study specifically focuses on teachers' cognition of traditional cultural values, customs, and practices. The theoretical foundation of this research is derived from cultural cognition theory and the technology acceptance model. The results indicate that preschool inclusive teachers' cognition of traditional culture has a significant positive impact on their digital literacy. Furthermore, traditional cultural cognition has an indirect effect on job insecurity, which influences the relationship between traditional culture and digital literacy. Technology acceptance serves as the first mediating variable between traditional cultural cognition and digital literacy, playing a crucial transmitting role. Meanwhile, job insecurity acts as the second mediating variable in this relationship. Together, technology acceptance and job insecurity form a chain-mediating effect in the relationship between traditional cultural cognition and digital literacy. Based on these findings, we propose recommendations such as constructing a cultural context, emphasizing technology acceptance, and enriching emotional support systems to create a favorable environment for improving preschool inclusive teachers' digital literacy. The unique value of this study lies in revealing the mechanism through which traditional cultural cognition influences digital literacy, providing empirical evidence for teacher training and policy-making.